STRUCTURAL ANALYSIS OF CONCRETE BUILDING SPACE EXPANSION WITH STEEL PORTAL REINFORCEMENT STRUCTURAL ANALYSIS OF SPACE EXPANSION OF CONCRETE BUILDING WITH RETROFITTING STEEL PORTAL - Andrisman Satria; Chaira; Yunita Arafah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Changes in the function of buildings often necessitate modifications to the structural form, requiring construction reinforcement to ensure stability and safety. This study aims to evaluate the effectiveness of structural reinforcement using steel in buildings undergoing functional changes. The methodology involves comparing the structural analysis of the existing building with the building after reinforcement. The research findings indicate that using IWF 250x125x6x9 steel as a reinforcement solution significantly enhances the structure's load-bearing capacity. In conclusion, the reinforcement of concrete beams with IWF 250x125x6x9 steel has proven effective in increasing the building's load capacity, thereby ensuring the building's safety and sustainability.